Estimation of the α/β ratio of non-small cell lung cancer treated with stereotactic body radiotherapy. (January 2020) - Klement, Rainer J.; Sonke, Jan-Jakob; Allgäuer, Michael; Andratschke, Nicolaus; Appold, Steffen; Belderbos, José; Belka, Claus; Dieckmann, Karin; Eich, Hans T.; Flentje, Michael; Grills, Inga; Eble, Michael; et al.
Highlights: The goal was to infer the α / β ratio in SBRTs for early stage NSCLC. We conducted a tumor control probability modeling study of almost 1300 SBRT cases. The LQ formalism appears valid for converting between SBRT schedules. Our results support most probable α / β estimates in the range 12–16 Gy. However, large uncertainties do not rule out α / β = 10 Gy. Abstract: Background: High-dose hypofractionated radiotherapy should theoretically result in a deviation from the typical linear-quadratic shape of the cell survival curve beyond a certain threshold dose, yet no evidence for this hypothesis has so far been found in clinical data of stereotactic body radiotherapy treatment (SBRT) for early-stage non-small cell lung cancer (NSCLC). A pragmatic explanation is a larger α / β ratio than the conventionally assumed 10 Gy. We here attempted an estimation of the α / β ratio for NSCLC treated with SBRT using individual patient data. Materials and methods: We combined two large retrospective datasets, yielding 1294 SBRTs (≤10 fractions) of early stage NSCLC. Cox proportional hazards regression, a logistic tumor control probability model and a biologically motivated Bayesian cure rate model were used to estimate the α / β ratio based on the observed number of local recurrences and accounting for tumor size. Results: A total of 109 local progressions were observed after a median of 17.7 months (range 0.6–76.3 months). Cox regression, logistic regression of 3 year tumor control probability and the cure rate model yielded best-fit estimates of α / β = 12.8 Gy, 14.9 Gy and 12–16 Gy (depending on the prior for α / β ), respectively, although with large uncertainties that did not rule out the conventional α / β = 10 Gy. Conclusions: Clinicians can continue to use the simple LQ formalism to compare different SBRT treatment schedules for NSCLC. While α / β = 10 Gy is not ruled out by our data, larger values in the range 12–16 Gy are more probable, consistent with recent meta-regression analyses.